Joint Power Control and Scheduling for High-Dynamic Multi-Hop UAV Communication: A Robust Mean Field Game - Tong Li; Chungang Yang; Lizhong Chang; Lingli Yang; Peng Gong; Haoxiang Dai; Jingyu Shen; Meng Wen; Zhu Han (IEEE Access)
As an extensive prospect in communication technology, multi-hop unmanned aerial vehicle (UAV) faces some challenges as well. How to ensure the availability of time slots in high dynamic scenarios and the rationality and robustness of power allocation in massive scenarios remains to be resolved. In this paper, we propose a robust mean field game (MFG) framework to manage time slot resources and power resources. On the one hand, this framework can predict the potential conflicts of time slots and avoid them in time. On the other hand, it can well adapt to the massive scenarios with complex interference, in order to realize power control. The simulation results show that the robust MFG-based resource management scheme can not only reduce the probability of packet collision and packet loss, but also improve communication energy efficiency (EE) with better robustness.